(untitled) (TAMADDUN NURI JURNALI, 2025)
This article presents information on the factors that positively influence the formation of a healthy lifestyle in national families, the fact that in raising a child, the mother must first of all adhere to certain ethnomedical procedures, and the manifestations of compliance with sanitary and hygienic requirements.